Batrachospermum keratophytum Bory emend. R.G. Sheath, M.L. Vis et K.M. Cole, a new freshwater red algal species for Ukraine - Vis, M.L.; Kapustin, D.A. (Альгология, 2009)
A noteworthy species of freshwater red algae, Batrachospermum keratophytum Bory emend.. R.G. Sheath, M.L. Vis et K.M. Cole, was record for the first time in the Ukraine. Information on the taxonomic position, description, and locations of B. keratophytum in the Ukraine is provided. Сообщается о нахождении нового для Украины вида пресноводных красных водорослей Batrachospermum keratophytum Bory emend.. R.G. Sheath, M.L. Vis et K.M. Cole. Приводится его систематическое положение, описание и местонахождения на территории Украины.